Handbook of Mathematical Models in Computer Vision - Paragios, Nikos; Chen, Yunmei; Faugeras, Olivier (Springer-Verlag, 2006)
This comprehensive volume is an essential reference tool for professional and academic researchers in the filed of computer vision, image processing, and applied mathematics. Continuing rapid advances in image processing have been enhanced by the theoretical efforts of mathematicians and engineers. This marriage of mathematics and computer vision - computational vision - has resulted in a discrete approach to image processing that is more reliable when leveraging in practical tasks. This comprehensive volume provides a detailed discourse on the mathematical models used in computational vision from leading educators and active research experts in this field. Topical areas include: image reconstruction, segmentation and object extraction, shape modeling and registration, motion analysis and tracking, and 3D from images, geometry and reconstruction. The book also includes a study of applications in medical image analysis. "Handbook of Mathematical Models in Computer Vision" provides a graduate-level treatment of this subject as well as serving as a complete reference work for professionals.